Debt Management : Now the Difficult Part - Gooptu, Sudarshan (World Bank, Washington, DC, 2012)
The first years of the 21st century were characterized by more prudent macroeconomic policies in the developing world, the positive impact of debt relief on low-income countries (LICs), and positive growth trends for the world economy, despite the puncturing of the high-tech "bubble" in Organization for Economic Co-operation and Development (OECD) countries. Until the eve of the financial crisis, many emerging economies were able to reduce the vulnerabilities of their debt portfolios and debt management was being carried out under favorable circumstances. Average maturities increased, reflecting increases in the maturities of new debt issuances, and rollover risks declined. Moreover, the increased availability of local currency financing, reflecting the development of domestic capital markets, and the globalization of the corporate sector in emerging economies underscored the changing landscape of development financing.